The Saffron Wave : Democracy and Hindu Nationalism in Modern India. - Hansen, Thomas Blom. (Princeton : Princeton University Press, 2001)
The rise of strong nationalist and religious movements in postcolonial and newly democratic countries alarms many Western observers. In The Saffron Wave, Thomas Hansen turns our attention to recent events in the world's largest democracy, India. Here he analyzes Indian receptivity to the right-wing Hindu nationalist party and its political wing, the Bharatiya Janata Party (BJP), which claims to create a polity based on "ancient" Hindu culture. Rather than interpreting Hindu nationalism as a mainly religious phenomenon, or a strictly political movement, Hansen places the BJP within the context.
Book Cover; Title; Copyright; Contents.
Print version record.
eBooks on EBSCOhost
Keywords: Hinduism and politics -- India; Nationalism -- Religious aspects -- Hinduism; India -- Politics and government -- 1977-; Hindouisme et politique -- Inde; POLITICAL SCIENCE -- Political Process -- Political Parties; RELIGION -- Hinduism -- General; Hinduism and politics; Nationalism -- Religious aspects -- Hinduism; Politics and government; India; Since 1977